2010
DOI: 10.2139/ssrn.1650246
|View full text |Cite
|
Sign up to set email alerts
|

A Phoenix in Flames? Portfolio Choice and Violence in Civil War in Rural Burundi

Abstract: This paper challenges the idea that farmers revert to subsistence farming when confronted with violence from civil war. While there is an emerging macroeconomic consensus that wars are detrimental to development, we find contrasting microeconomic evidence. Using several rounds of (panel) data at the farm and community level, we find that farmers in Burundi who are confronted with civil war violence in their home communities increase export and cash crop growing activities, invest more in public goods and revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…A study on the conflict-affected parts of Northern Uganda by Rockmore (2012) suggests that conflict alters the composition of assets held towards less risky assets. Our findings are qualitatively similar to that of Nillesen and Verwimp (2010) for post-conflict rural Burundi, where the cultivation of cash crops also increased. In our case, the past experience of conflict and a fear of communal violence igniting in the future raise the probability of mixed crop production.…”
Section: Production Decisions: Cropping Patternssupporting
confidence: 84%
“…A study on the conflict-affected parts of Northern Uganda by Rockmore (2012) suggests that conflict alters the composition of assets held towards less risky assets. Our findings are qualitatively similar to that of Nillesen and Verwimp (2010) for post-conflict rural Burundi, where the cultivation of cash crops also increased. In our case, the past experience of conflict and a fear of communal violence igniting in the future raise the probability of mixed crop production.…”
Section: Production Decisions: Cropping Patternssupporting
confidence: 84%
“…Equally, while owing livestock may be a profitable and secure economic strategy in peace times, it may become quite risky in wartimes due to the collapse of markets, services or the danger of theft (Bundervoet 2006;Verpoorten 2009). Using data from Burundi, Nillesen and Verwimp (2010) however challenge the idea that farmers resort to subsistence in a post-conflict setting. Detailed and comparable registration of the different types of economic activities before, during and after conflict can help to address this issue in future research.…”
Section: Crops and Livestockmentioning
confidence: 98%
“…Empirical evidence on the changes in production and investment decisions caused by violence in conflict regions is largely absent. Economic research has found that the threat or anticipation of future shocks, like violence, pushes rural household to revert back to subsistence agriculture and shift portfolio to less risky, but also less profitable activities (Deininger, 2003;Nillesen & Verwimp, 2010). Rural households also increase participation in informal credit markets and recur to precautionary savings (Binzel & Brück, 2007;Brück, 2004).…”
Section: Agricultural Production Economic Risk and The Risk Of Violencementioning
confidence: 99%
“…Even though an interior solution is feasible, there exist two corner solutions in a violent state. On the one hand, if the punishment constraint is still binding ( ) and the economic risk is high, a state of violence pushes the farmer to allocate all the land to the risk-free crop, that is, farmers are pushed to revert back to subsistence agriculture (Deininger, 2003;Nillesen & Verwimp, 2010). On the other hand, if the punishment constraint does not bind ( ) or, equivalently, the expected return of the illegal crop is much larger than the punishment ( ( ) ), farmers will have enough incentive to abandon export crop cultivation and allocate the land between the risk-free and the illegal crop.…”
Section: A Theoretical Model Of Farm Allocation Under Economic Risk Amentioning
confidence: 99%
See 1 more Smart Citation